Information attitude of book editors and productivity in the publishing firms in South-West, Nigeria (2020)
The publishing industry is a vital index of a nation's development. It makes its contribution to national growth through its productivity, and a key agent of this productivity is the editor. The editor forms the nucleus of the publishing firm. He/she is the nerve of the publishing operations and is highly indispensable in the publishing processes. However, information is germane to editorial activities and as such he/she cannot perform optimally without having requisite information. This thus implies that editor must seek for information. Information-seeking entails requisite and appropriate disposition which is otherwise called attitude. The attitude of editors, the type as well as source of information are all important for editorial efficiency. It is these issues of information attitude of editors and their productivity that this study seeks to answer. Survey method was adopted for the study, structured questionnaire was the instrument employed for data collection while three research questions were formulated. The study population was 62 educational publishing firms in South-West Nigeria while the sample for the study was the 205 editorial staff of twenty randomly selected publishing houses which constituted 19.4 %. The data collected were analysed using Statistical Package for the Social Science (SPSS) version 21. Mean and standard deviation were determined for continuous variables while frequencies and percentages were carried out on categorical variables. The results were presented in tables and charts. The study recommended that editors should obtain information on production, explore the Internet and social media more effectively and strive for more editorial competence to attain higher productivity. Structured into seven parts; the paper is discussed under the following subheadings: introduction, literature review, theoretical framework, methodology, analysis and discussion, conclusion and recommendations.